2022
DOI: 10.3390/v15010117
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity, Stability and Molecular Characterization of Eight Potent Bacteriophages Infecting Carbapenem-Resistant Klebsiella pneumoniae

Abstract: Background: Members of the genus Klebsiella are among the leading microbial pathogens associated with nosocomial infection. The increased incidence of antimicrobial resistance in these species has propelled the need for alternate/combination therapeutic regimens to aid clinical treatment, including bacteriophage therapy. Bacteriophages are considered very safe and effective in treating bacterial infections. In this study, we characterize eight lytic bacteriophages that were previously isolated by our team agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
0
0
0
Order By: Relevance
“…The adsorption profile of phage KP1LMA showed that after 10 and 60 min, approximately 60 and 75% of the phage particles were adsorbed to the host cells, respectively, with an adsorption constant of K= 4.23246 × 10 −10 mL −1 min −1 . Similar results have been obtained with phage K2a [42]. However, in general, the adsorption rate of phage KP1LMA is lower than in other studies for Klebsiella phages [24,42,43].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The adsorption profile of phage KP1LMA showed that after 10 and 60 min, approximately 60 and 75% of the phage particles were adsorbed to the host cells, respectively, with an adsorption constant of K= 4.23246 × 10 −10 mL −1 min −1 . Similar results have been obtained with phage K2a [42]. However, in general, the adsorption rate of phage KP1LMA is lower than in other studies for Klebsiella phages [24,42,43].…”
Section: Discussionsupporting
confidence: 87%
“…Similar results have been obtained with phage K2a [42]. However, in general, the adsorption rate of phage KP1LMA is lower than in other studies for Klebsiella phages [24,42,43]. Phage LASTA and SJM3 adsorption assays showed that approximately 97 and 94%, respectively, of the phage particles were adsorbed to K. pneumoniae after 20 min [24].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Однако при пероральном приеме жидких лекарственных форм фаговых препаратов происходит их значительная инактивация под воздействием кислой среды желудочного сока [3]. Существующая проблема недостаточной стабильности характеристик препаратов бактериофагов и снижение их титра обусловливают необходимость учитывать кислотно-щелочные условия, а также влияние иных факторов в желудочно-кишечном тракте при разработке состава пероральных форм препаратов бактериофагов [4]. С целью устранения указанных недостатков на предприятии АО «НПО «Микроген» (филиал в г. Пермь «Пермское НПО «Биомед») разработан лекарственный препарат Секстафаг® Пиобактериофаг поливалентный в форме капсул, обеспечивающих сохранение литической активности бактериофага [5].…”
Section: Introductionunclassified